The antibacterial activities and chemical composition of extracts from Carica papaya cv. Sekaki/Hong Kong seed - Muhamad, S. A. S.; Bakar, Jamilah; Abdul Rahman, Russly; A., Faridah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Ten solvents were used to extract phytochemicals from the peel of Carica papaya cv. Sekaki/Hong Kong to evaluate antibacterial activities and determine chemical composition of Carica papaya cv. Sekaki/Hong Kong seeds. The antibacterial activities of ten solvent extracts were tested against 14 microorganisms vis Shigella sonnei, Salmonella typhimurium, Escherichia coli, Salmonella enteritidis, Vibrio vulnificus, Vibrio parahaemolyticus, Proteus mirabilis, Staphylococcus aureus, Bacillus cereus, Listeria monocytogenes, Corynebacterium diphtheria, Clostridium perfringens, Streptococcus pneumoniae and Bacillus subtilis using disk diffusion test (DDT). The Carica papaya seed of ACN and MeOH extracts inhibited 11 microorganisms, indicating their broad spectrum activity. The disk diffusion test exhibited moderate and clear inhibition on C. diphtheria, S. pneumonia, B. subtilis and C. perfringens. MeOH extract inhibited S. enteritidis, V. vulnificus, P. mirabilis and B. cereus with the lowest MIC at 11.25 mg/mL each, thus was chosen as the best extract. The hierarchy of extract potency can be ranked as MeOH > acetone > ACN > CHCL3 > hexane > DE = PE > EtOH > DCM based on clear and moderate inhibition and the lowest MIC. TPC and TFC of the extracts ranged between 4.83 to 22.59 mg GAE/g DW and 1.32 (water) and 17.15 mg QE/g DW respectively. The GC/MS analysis of MeOH extract identified potential antibacterial compounds such as isothiocyanatomethyl benzene, 9-octadecenoic acid, hexadecanoic acid and β-sitosterol. The Carica papaya seed cv. Sekaki/ Hong Kong possessed significant antibacterial activities when extracted by different solvents in particular MeOH solvent.